Notary's Responsibility for the Denial of Signature of A Letter Under the Hand that Legalized Before A Notary - Dinda Putri yani (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2023)
The notary is responsible for what he has made in accordance with the duties and powers that a notary must carry out. The authority of a Notary is stated in Article 15 paragraph (1) of Law No. 2 of 2014, and besides that, the authority to do authentic deeds, Article 15 paragraph (2) of Law Number 2 of 2014 concerning the Position of Notary which states that a Notary has the authority to